2021
DOI: 10.3390/su13115942
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characterisation and the Prospects of Biofuel Production from Rubberwood Sawdust and Sewage Sludge

Abstract: This study aims to evaluate the physicochemical properties of rubberwood sawdust (RWS) and sewage sludge (SS) for producing biofuel or liquid products via pyrolysis and co-pyrolysis. The chemical and thermal properties of both samples were observed to have superior bioenergy production capabilities. RWS and SS had significantly different physicochemical properties, such as particle-size distribution, bulk density, ultimate and proximate analysis, lignocellulose composition, thermal-degradation behaviour, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…A lower C content (48.4% DM) was determined in Pinus sp. sawdust in China [55] and in Hevea brasiliensis sawdust (48.5% DM) obtained from a wood processing plant [56]. Betula pendula wood chips also contained less C (50.4% DM) [57].…”
Section: Elemental Compositionmentioning
confidence: 99%
“…A lower C content (48.4% DM) was determined in Pinus sp. sawdust in China [55] and in Hevea brasiliensis sawdust (48.5% DM) obtained from a wood processing plant [56]. Betula pendula wood chips also contained less C (50.4% DM) [57].…”
Section: Elemental Compositionmentioning
confidence: 99%
“…Notwithstanding, the bio-oil yields can serve as alternative fuel to the fossil fuel in industrial operations such as in boiler engines. This is an improvement on fossil fuels and is also considerably more environmentally friendly [59].…”
Section: Performance Criteria For Error Computationmentioning
confidence: 99%
“…Criteria for the quality of biofuels registered in the literature include high percentages of C and O in biomass, as this favors calorific value [ 48 , 49 ]. This affirmation must be qualified; however, because Ali et al [ 50 ] reported that lignocellulosic materials with high O content can corrode combustion equipment. Hydrogen, in contrast, has been found to contribute positively to calorific value, though its proportion in biomass is lower than that of C [ 48 ].…”
Section: Resultsmentioning
confidence: 99%